Factors That Cause Denial of Iddah (Waiting Period), Entitlements: A Case Study of Kano State, Nigeria - Anas, Mohd Yunus; Sa`idu Ibrahim, Sulaiman (2016)
The study is to identify the reasons that cause the divorced husband did not allowed his wife to enjoy her entitlements during her iddah (waiting period) as it is provided by the Islamic law, until the expiration of three consecutive menstruation periods or months. In Islamic law is well known that the divorced woman should stay in the marital home after sentenced her divorced from sometimes known as iddah period of waiting, during this time the husband is to provide clothes, food, shelter and some other life felicity. Two hundred divorced men and women were served with the questionnaires administered in English and Hausa languages, respectively which has been answered by the divorced men and women.